Implementasi Kurikulum Merdeka di TK Aisyiah Bustanul Athfal IV Kota Jambi: - Simanjuntak, Ade Veni Yunianti; Apriliana, Kasih; Murni, Kaila; EF, Dinda Filawati; Harianja, Sri Indriani; Utami, Winda Sherly (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2024)
This research aims to obtain information about the implementation of the Independent Curriculum and the challenges teachers face in implementing the curriculum. The place where this research was carried out was Aisyiah Bustanul Athfal IV Kindergarten, Jambi City as one of the Driving Schools. This type of research is descriptive qualitative research. The data collection method in this research uses techniques, namely interviews, direct observation and document collection. The research results show that the Aisyiah Bustanul Athfal IV Kindergarten in Jambi City has successfully implemented the Independent Curriculum through three stages, namely preparation, implementation and evaluation. At the planning stage, the Principal collaborates with teachers to develop the Educational Unit Operational Curriculum (KOSP), Teaching Module, and Project Module for Strengthening the Pancasila Student Profile (P5).